Accuracy of bone‐level assessments following reconstructive surgical treatment of experimental peri‐implantitis. Issue 4 (16th February 2022) - Almohandes, Ahmed; Lund, Henrik; Carcuac, Olivier; Petzold, Max; Berglundh, Tord; Abrahamsson, Ingemar
Abstract: Aims: The purpose of this study was to evaluate the accuracy of bone‐level assessments using either cone‐beam computed tomography (CBCT), intra‐oral peri‐apical (PA) radiographs or histology following reconstructive treatment of experimental peri‐implantitis. Materials and Methods: Six Labrador dogs were used. Experimental peri‐implantitis was induced 3 months after implant placement. Surgical treatment of peri‐implantitis was performed and peri‐implant defects were allocated to one of four treatment categories; no augmentation, bone graft materials with or without a barrier membrane. Six months later, intra‐oral PA radiographs and block biopsies from all implants sites were obtained. Marginal bone levels (MBLs) were measured using PA radiographs, CBCT and histology. Results: Significant correlations of MBL assessments were observed between the three methods. The measurements in PA radiographs consistently resulted in an overestimation of the bone level of about 0.3–0.4 mm. The agreement between the methods was not influenced by the use of bone substitute materials in the management of the osseous defects. Conclusions: Although MBL assessments obtained from PA radiographs showed an overestimation compared to MBL assessments on corresponding CBCT images and histological sections, PA radiographs can be considered a reliable technique for peri‐implant bone‐level evaluations following reconstructive surgical therapy of experimental peri‐implantitis.